Perceived wages and the gender gap in STEM fields - Aderonke Osikominu; Gregor Pfeifer (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
We estimate gender differences in elicited wage expectations among German University students applying for STEM and non-STEM fields. Descriptively, women expect to earn less than men and also have lower expectations about wages of average graduates across different fields. Using a two-step estimation procedure accounting for self-selection, we find that the gender gap in own expected wages can be explained to the extent of 54-69% by wage expectations for average graduates across different fields. However, gender differences in the wage expectations for average graduates across different fields do not contribute to explaining the gender gap in the choice of STEM majors.
urn:nbn:de:bsz:100-opus-14656
Keywords: I21; J16; J31; 330; gender gap; wage expectations; college major choice; STEM